AKTing on XPO1 inhibition in AML - Göllner, Stefanie; Müller-Tidow, Carsten (Nature cancer, 2022)
Inhibition of XPO1-mediated nuclear export by selinexor represents a promising therapeutic strategy in acute myeloid leukemia. Because XPO1 is not specific for tumor-suppressive proteins, selinexor may also activate pro-oncogenic processes. A study now shows that inhibition of selinexor-induced, purinergic receptor-mediated AKT activation potentiates its anti-leukemic activity.